Respons Pertumbuhan Sambung Pucuk Tanaman Kelengkeng (Dimocarpus longan L.) terhadap Lama Perendaman Entres pada Air Kelapa Muda - Wardhani, Silvia; Kusumaningrum, Nora Augustien; Pribadi, Didik Utomo (JURNAL AGROTROPIKA, 2024)
The decline in domestic productivity of longan (Dimocarpus longan L.) occurred due to increased imports. Efforts to get seedlings quickly without requiring a long time can be done by vegetative propagation of longan (shoot grafting). The purpose of this study was to obtain a combination of soaking time with the right concentration of young coconut water on the growth of shoots. The research was conducted from April to July 2023 at Kebun Mangga Pohjentrek, Pasuruan. This study used a 4x4 factorial pattern arranged in a completely randomized design (CRD) with three replications.  There are 2 factors studied, the first factor is the duration of immersion of the scion consisting of 4 levels (0, 2, 4, 6 hours). The second factor is the concentration of young coconut water consisting of 4 levels (0%, 25%, 50%, 75%). The parameters observed were bud break, percentage of finished grafts, bud length, bud diameter, and number of leaves. The results showed that there was an interaction between the combination of soaking time of 4 hours with a concentration of 25% on the length of shoots at 28 DAG. Effective growth is obtained at a soaking time of 4 hours and a concentration of 25% young coconut water on the parameters of shoot length and shoot diameter.Keywords : scion, longan, concentrate coconut water, shoot grafting